Systemic deficits in lipid homeostasis promote aging-associated impairments in B cell progenitor development - Silvia Vicenzi; Fangyuan Gao; Parker Côté; Joshua D. Hartman; Lara C. Avsharian; Ashni A. Vora; R. Grant Rowe; Hojun Li; Dorota Skowronska-Krawczyk; Leslie A. Crews (GeroScience, 2025)
Organismal aging has been associated with diverse metabolic and functional changes across tissues. Within the immune system, key features of physiological hematopoietic cell aging include increased fat deposition in the bone marrow, impaired hematopoietic stem and progenitor cell (HSPC) function, and a propensity towards myeloid differentiation. This shift in lineage bias can lead to pre-malignant bone marrow conditions such as clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenias of undetermined significance (CCUS), frequently setting the stage for subsequent development of age-related cancers in myeloid or lymphoid lineages. Human aging has also been associated with diverse lipid alterations across tissues, such as decreased phospholipid membrane fluidity that arises as a result of increased saturated fatty acid (FA) accumulation and a decay in n-3 polyunsaturated fatty acid (PUFA) species by the age of 80 years, however the extent to which impaired FA metabolism contributes to hematopoietic aging is less clear. Here, comprehensive multi-omics analyses uncovered a role for a key PUFA biosynthesis gene, ELOVL2 , in mouse and human immune cell aging. Whole transcriptome RNA-sequencing studies and complementary flow cytometric analyses of bone marrow from aged Elovl2 mutant (enzyme-deficient) mice compared with age-matched controls revealed global downregulation in lymphoid cell markers and expression of genes involved specifically in B cell development. These studies unveiled CD79B, a vital molecular regulator of lymphoid progenitor development from the pro-B to pre-B cell stage, as a putative surface biomarker whose loss is associated with accelerated immune aging. The lipidome of mutant versus wild-type mice also displayed significant changes in the biophysical properties of cellular membranes. To investigate the relevance of these finding to human bone marrow aging, analyses of a single cell RNA-seq dataset of human HSPCs across the spectrum of human development and aging uncovered a rare subpopulation (< 7%) of CD34 + HSPCs that expresses ELOVL2 in healthy adult bone marrow. This HSPC subset, along with CD79B -expressing lymphoid-committed cells, were almost completely absent in CD34 + cells isolated from elderly bone marrow samples. Together, these findings uncover new roles for lipid metabolism enzymes in the molecular regulation of cellular aging and immune cell function in mouse and human hematopoiesis. In addition, because systemic loss of ELOVL2 enzymatic activity resulted in downregulation of B cell genes that are also associated with lymphoproliferative neoplasms, this study sheds light on an intriguing metabolic pathway that could be leveraged in future studies as a novel therapeutic modality to target blood cancers or other age-related conditions involving the B cell lineage.

Corrigendum to “Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity” [Carbohydr. Polym. 347 (1 January 2025) 122686] - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Collision activity during training increases total energy expenditure measured via doubly labelled water - Nessan Costello; Kevin Deighton; Thomas Preston; Jamie Matu; Joshua Rowe; Thomas Sawczuk; Matt Halkier; Dale B. Read; Daniel Weaving; Ben Jones (European Journal of Applied Physiology, 2018)

Lethal concentrations of suspended solids for common native fish species that are rare in New Zealand rivers with high suspended solids loads - David K. Rowe; Murray Hicks; Joshua P. Smith; Erica Williams (New Zealand Journal of Marine and Freshwater Research, 2009)
Common native fish species that are rare in New Zealand rivers with high suspended solids (SS) concentrations were identified to determine which species were likely to be most affected by high SS concentrations. Mortality rates for the three most sensitive species (banded kokopu Galaxias fasciatus, redfin bully Gobiomorphus huttoni, common smelt Retropinna retropinnd ) were measured over a range of SS concentrations to identify lethal concentrations. The survival of banded kokopu and redfin bully was not reduced by SS concentrations up to 43 000 g m −3 ; however, the 24‐h survival of common smelt was reduced by SS concentrations over 1000 g m −3 , and its median lethal concentration (LC50) was close to 3000 g m −3 . SS concentrations over 3000 g m −3 for more than 24 h will therefore reduce smelt but not affect the mortality of most other common native fish species. Although mortality from high concentrations of SS can account for the scarcity of smelt in rivers with high SS concentrations, mortality from high SS does not explain the scarcity of banded kokopu or redfin bully in such rivers. High turbidity (>20 nephelometric turbidity units) is known to limit the upstream migration and recruitment of juvenile banded kokopu in rivers with increased SS concentrations. Banded kokopu is therefore affected by increased turbidity from SS rather than lethal SS concentrations. As redfin bully were not affected by either high turbidity levels or high SS concentrations, the low abundance of this species in rivers with high SS concentrations is likely to be related to the siltation of benthic habitats.

Use of in‐stream cover types by adult banded kokopu ( Galaxias fasciatus ) in first‐order North Island, New Zealand, streams - David K. Rowe; Joshua Smith (New Zealand Journal of Marine and Freshwater Research, 2003)
The relative importance of wood material in providing in‐stream cover for adult banded kokopu ( Galaxias fasciatus ) was determined in first‐order, North Island, New Zealand, streams. Three groups of streams, each differing in the relative amount of three types of in‐stream cover (i.e., wood, boulders, undercut banks) were selected and banded kokopu were sampled in their pools using electric fishing. Banded kokopu occurred beneath boulders, undercut banks, and wood material in all pools except those lacking any in‐stream cover, or those where large (total length >400 mm) eels were present. Their presence in pools was therefore highly dependent on in‐stream cover, provided large eels were absent. In streams where the cover provided by boulders was lacking, banded kokopu selected mainly undercut banks and wood. However, in streams containing large amounts of bank and boulder cover, wood was under‐utilised, indicating that it was least preferred. In pools providing a choice of cover types, bank cover was more frequently used than other types, indicating that it is preferred. The mean size of banded kokopu in pools was positively related to their relative abundance, and their abundance was in turn related to habitat quality as defined by in‐stream cover. Streams with the least amount of bank cover had the lowest number of pools occupied by banded kokopu, fewer banded kokopu per pool, fewer pools containing two or more banded kokopu, and the smallest banded kokopu. Collectively, these data indicate that bank cover in pools provides optimal habitat for banded kokopu, and that wood material was important only where other types of more permanent cover were lacking. Logs and wood slash from logging operations could therefore be important for increasing banded kokopu habitat in logged streams where bank and boulder cover are scarce.

Effects of turbidity on the ability of juvenile rainbow trout, Oncorhynchus mykiss , to feed on limnetic and benthic prey in laboratory tanks - David K. Rowe; Tracie L. Dean; Erica Williams; Joshua P. Smith (New Zealand Journal of Marine and Freshwater Research, 2003)
The feeding rate of juvenile rainbow trout, Oncorhynchus mykiss Richardson, 1836, on small (1–2 mm diam.) Daphnia spp. in laboratory tanks was not reduced by turbidity levels up to 160 Nephelometric Turbidity Units (NTU). Furthermore, the high feeding rates on larger, benthic prey (viz. Deleatidium spp. and chironomid larvae) in clear water (0 NTU) were maintained at turbidities up to 160 NTU. Therefore, any impairment of vision by increased turbidity did not affect the ability of trout to feed on these prey, and non‐visual senses may be used for the capture of such prey in turbid waters. Although trout were strongly size‐selective for both large chironomid and Deleatidium larvae in clear water, turbidities over 20 and 160 NTU, respectively, reduced size‐selection. Vision is therefore needed by trout to select larger prey. However, chironomid larvae were consumed by trout in the complete absence of light, so their ability to capture these prey in tanks was not dependent on visual cues. It is apparent that trout do use other senses such as the lateral line system to detect and capture such prey when turbidity levels are high and when light levels or water clarity are low. This ability is expected to offset any reduction in visual feeding caused by increased turbidity, and it helps explain the increased emphasis on epibenthic feeding by trout in turbid waters.

Effects of logging with and without riparian strips on fish species abundance, mean size, and the structure of native fish assemblages in Coromandel, New Zealand, streams - David K. Rowe; Joshua Smith; John Quinn; Ian Boothroyd (New Zealand Journal of Marine and Freshwater Research, 2002)
We determined the effects of logging, both with and without a riparian buffer strip, on the native fish fauna at 27 stream sites in an exotic pine (mainly Pinus radiata) forest on the Coromandel Peninsula, New Zealand. Fish abundance at the logged sites was compared with reference sites in both unlogged pine and native forest. The abundance of Anguilla dieffenbachii (Gray) and Anguilla australis (Richardson) was not significantly affected by logging. However, the abundance of Galaxias fasciatus (Gray) and Gobiomorphus huttoni (Ogilby) was. There were fewer Ga. fasciatus at the logged sites without buffers than at the reference sites, but more at the logged sites with buffers. The abundance of Go. huttoni was higher at the logged sites than at the reference sites, and was highest at the logged sites with riparian buffers. Overall, the different, species‐specific responses to logging maximised total fish numbers at the logged sites. As total fish numbers, the abundance of Ga. fasciatus , and species equitability, a measure of fish assemblage structure, were all highest at the logged sites with riparian buffer strips, we concluded that riparian strips enhanced the native fish community of streams within these logged catchments.

Effects of turbidity on the feeding ability of adult, riverine smelt ( Retropinna retropinna) and inanga ( Galaxias maculatus) - David K. Rowe; Joshua Smith; Erica Williams (New Zealand Journal of Marine and Freshwater Research, 2002)
Laboratory tank experiments indicated that turbidity levels up to 160 Nephelometric Turbidity Units (NTU) did not reduce the feeding rates of adult smelt ( Retropinna retropinna Richardson), or inanga (Galaxias maculatus Jenyns), on Daphnia sp. Mean feeding rates were higher for inanga than for smelt. However, the lower rates for smelt were related to the greater variation in individual feeding rates. Specifically, a few fish fed intensively while most did not. As the feeding ability of both species was unaffected by turbidity levels up to 160 NTU, they were less sensitive to turbidity than juvenile banded kokopu ( Galaxias fasciatus Gray). Juvenile banded kokopu should therefore be used as the benchmark species for setting turbidity guidelines to protect native fish in rivers where this species is present. Both juvenile and adult rainbow trout ( Oncorhynchus mykiss Richardson) appear to be more sensitive to turbidity than adult inanga and smelt, so should be used as benchmark species in all other waters.

Effects of turbidity on the migration of juvenile banded kokopu ( Galaxias fasciatus ) in a natural stream - Jody Richardson; David K. Rowe; Joshua P. Smith (New Zealand Journal of Marine and Freshwater Research, 2001)
Laboratory experiments have shown that the juvenile migratory stage of banded kokopu ( Galaxias fasciatus (Gray 1842)) is more sensitive to turbidity than other native fish species and avoids turbidity levels of >25 nephelometric turbidity units (NTU). Field trials using juvenile fish collected from the Tarawera River and Hays Stream, New Zealand, were used to test the results from these laboratory experiments by measuring the effects of turbidity on the migration direction and rate for banded kokopu in a natural stream setting. In the stream setting, neither the migration rate nor the migration direction were affected at turbidity